The Contextual Curriculum: Learning in the Matrix, Learning From the Matrix. (November 2018) - Schrewe, Brett; Ellaway, Rachel H.; Watling, Christopher; Bates, Joanna
Abstract : Changes in the health care landscape over the last 25 years have led to an expansion of training sites beyond the traditional academic health sciences center. The resulting contextual diversity in contemporary medical education affords new opportunities to consider the influence of contextual variation on learning. The authors describe how different contextual patterns in clinical learning environments—patients, clinical and educational practices, physical geography, health care systems, and culture—form a contextual learning matrix. Learners' participation in this contextual matrix shapes what and how they learn, and who they might become as physicians. Although competent performance is critically dependent on context, this dependence may not be actively considered or shaped by medical educators. Moreover, learners' inability to recognize the educational affordances of different contexts may mean that they miss critical learning opportunities, which in turn may affect patient care, particularly in the unavoidable times of transition that characterize a professional career. Learners therefore need support in recognizing the variability of learning opportunities afforded by different training contexts. The authors set out the concept of the contextual curriculum in medical education as that which is learned both intentionally and unintentionally from the settings in which learning takes place. Further, the authors consider strategies for medical educators through which the contextual curriculum can be made apparent and tangible to learners as they navigate a professional trajectory where their environments are not fixed but fluid and where change is a constant.